CORRELATION BETWEEN PHYSICAL ACTVITIY AND SLEEP QUALITY IN MEDICAL STUDENTS DURING COVID-19 PANDEMIC - Azriel Siloam; I Putu Gede Adiatmika; I Dewa Ayu Inten Dwi-Primayanti; Luh Putu Ratna Sundari (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
A downward trend of physical activity level within the population of college students was observed during the COVID-19 pandemic. Various adjustments within their daily habits caused changes to the population’s sleep quality and physical activity level. The purpose of this study is to research the correlation between physical activity level and sleep quality in preclinical medical students in Udayana University. This study was conducted using an analytic cross-sectional method and consecutive sampling technique involving 282 preclinical medical students of Udayana University from academic year of 2018, 2019, and 2020. The data were obtained via the scores of Global Physical Activity Questionnaire and Pittsburgh Sleep Quality Index. The GPAQ score showed that 123 (43.6%), 127 (45%), and 32 respondents (11.4%) respectively had a low, moderate, and high level of physical activity. Meanwhile, the PSQI score showed that 102 respondents (36.2%) had a good sleep quality and 180 respondents (63.8%) had a bad sleep quality. The average PSQI score of the respondents was 5.23 (cut off = 5). The correlation between the level of physical activity and sleep quality was analyzed using the Chi-Square method and was deemed insignificant (p = 0.172; 2-sided). The majority of preclinical medical students had low-to-moderate level of physical activity and bad sleep quality. No significant correlation was found between level of physical activity and sleep quality in preclinical medical students during the COVID-19 pandemic. Further studies are needed to determine other factors that might affect physical activity level and sleep quality within the population. Keywords : Physical Activity Level; Sleep Quality; GPAQ; PSQI; COVID-19